Prototipe Sistem Pendekesi Pelangaran Zebra Cross Pada Traffic Light Berbasis Internet Of Things - Indra Gunawan; Aris Sudianto; Uswatun Hasanah (Fakultas Teknik Universitas Hamzanwadi, 2023)
In this era, the development of technology in the field of transportation is growing rapidly. This causes the number of vehicles used to facilitate the activities of most people, the need for private vehicles also increase. This condition is increasingly causing overcrowding, especially in rural and urban areas. In order to prevent overcrowding of these vehicles and reduce the rate of accidents on the highway, a traffic light or commonly called a traffic light is needed at every intersection or crossroads. Traffic lights are lights that control and regulate the flow that occurs in traffic. But most motorists lack in obeying traffic rules. In traffic regulations, there is also a zebra cross facility, which serves as a marker for motorists that there is a path for pedestrians to cross the road. However, in reality, even though the number of zebra crossings is quite large and has a size that can be seen, it doesn't seem to work properly. This phenomenon occurs because the increase in the number of motorized vehicles is not accompanied by an increase in public awareness. So we need a tool to make it easier for pedestrians to pass the zebra cross and provide convenience for officers to monitor traffic violations. The tool is a prototype of a motorist violation detection device passing through a zebra cross based on Internet of Things technology using the infrared Proximity Sensor E18-D80NK which is used to detect objects within a distance of 3-80 cm, the buzzer will issue an alarm sound as a warning to comply with traffic regulations in accordance with set. ESP32-Cam to capture images when the driver persists in violating traffic signs and the image will be sent via telegram.